DEVOTION IN THE FOLK LITERATURE OF PANDIT JAGANNATH - Navita; Sharmila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Pandit Jagannath has been a famous folk poet of Haryana who is also known as "Chhota Lakhmichand". Pandit Jagannath holds a prominent place in folk literature and devotion is prominently reflected in his works. Bhakti literature is an important part of Indian folk culture in which there is an expression of love, dedication and spirituality towards God. Similar devotion is also seen in the works of Pandit Jagannath, where he expresses his devotion and faith towards God in simple and lively language. There is a deep spiritual approach in his works where the inclusion of folk language and folk cultures makes his devotional literature even more impressive. This type of literature mentions the glory of God, religious stories and purification of a person's soul. His works are written for the general public, due to which they work to spread religious and spiritual awareness. His works are not only focused on devotion; but various aspects of folk life have also been highlighted in them.